Lead biosorption onto waste beer yeast by-product, a means to decontaminate effluent generated from battery manufacturing industry - Parvathi, Krishnakumar; Nagendran, Ramachandramurthy; Nareshkumar, Radhakrishnan (Electronic Journal of Biotechnology, 2007)
This paper projects the potential of waste beer yeast Saccharomyces cerevisiae in biosorbing lead from battery manufacturing industrial effluent. Experiments were carried out as a function of pH, biosorbent concentration, lead concentration and agitation speed. Specific lead uptake of 2.34 mg/g was recorded and the data gave good fits for Freundlich and Langmuir models with Kf and Qmax values of 0.5149 and 55.71 mg/g. The roles played by amines, carboxylic acids, phosphates, sulfhydryl group and lipids in lead biosorption were studied. Electrostatic attraction may be the mechanism of biosorption. The extent of contribution of the functional groups and lipids to lead biosorption was in the order: carboxylic acids > lipids > amines > phosphates. Blocking of sulfhydryl group did not have any significant effect on lead uptake.